Curcumin modulates nuclear factor kB (NF-KB)-mediated inflammation in human tenocytes in vitro: Role of the PHOSPHATIDYLINOSITOL 3-KINASE/Akt PATHWAY - Buhrmann, Constanze; Mobasheri, Ali; Busch, Franziska; Aldinger, Constance; Stahlmann, Ralf; Montaseri, Azadeh; Shakibaei, Mehdi (American Society for Biochemistry and Molecular Biology, 2011)
Inflammatory processes play essential roles in the pathogenesis of tendinitis and tendinopathy. These events are accompanied by catabolic processes initiated by pro-inflammatory cytokines such as interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α). Pharmacological treatments for tendinitis are restricted to the use of non-steroidal anti-inflammatory drugs. Recent studies in various cell models have demonstrated that curcumin targets the NF-κB signaling pathway. However, its potential for the treatment of tendinitis has not been explored. Herein, we used an in vitro model of human tenocytes to study the mechanism of curcumin action on IL-1β-mediated inflammatory signaling. Curcumin at concentrations of 5-20 μm inhibited IL-1β-induced inflammation and apoptosis in cultures of human tenocytes. The anti-inflammatory effects of curcumin included down-regulation of gene products that mediate matrix degradation (matrix metalloproteinase-1, -9, and -13), prostanoid production (cyclooxygenase-2), apoptosis (Bax and activated caspase-3), and stimulation of cell survival (Bcl-2), all known to be regulated by NF-κB. Furthermore, curcumin suppressed IL-1β-induced NF-κB activation via inhibition of phosphorylation and degradation of inhibitor of κBα, inhibition of inhibitor of κB-kinase activity, and inhibition of nuclear translocation of NF-κB. Furthermore, the effects of IL-1β were abrogated by wortmannin, suggesting a role for the phosphatidylinositol 3-kinase (PI-3K) pathway in IL-1β signaling. Curcumin suppressed IL-1β-induced PI-3K p85/Akt activation and its association with IKK. These results demonstrate, for the first time, a potential role for curcumin in treating tendon inflammation through modulation of NF-κB signaling, which involves PI-3K/Akt and the tendon-specific transcription factor scleraxis in tenocytes.